Patients with hydrocephalus presenting in the psychiatric clinic: report of two cases - Wolfgang W. May (Arquivos de Neuro-Psiquiatria)
Two patients with major mental symptomatology and few neurological signs were presented who on further studies were revealed to have unsuspected hydrocephalus. This was due to an obstructive lesion at the level of the aqueduct present since birth or for many years. Both presented with a rather unusual clinical picture so that they were first considered to suffer from a psychiatric illness. Radiographic contrast studies established the diagnosis in both cases and led to successful treatment in one of them. The first patient made an uneventful recovery after a shunting operation. The other had no such operation and died of an unrelated disease some time later. A constellation of declining mental functions with or without behavioral disturbance and few or minor neurologic signs and an abnormal electroencephalogram should include in the differential diagnosis "occult" hydrocephalus which is a potentially correctable condition. The psychiatrist might be the first one to see this type of patient and to initiate the appropriate evaluation.